Characterization of Internal Validity Threats to Phase III Clinical Trials for Chemotherapy-Induced Peripheral Neuropathy Management: A Systematic Review - Deborah Lee; Grace Kanzawa-Lee; Robert Knoerl; Gwen Wyatt; Ellen M. Lavoie Smith (Elsevier, 2019)
Objective: The recent American Society of Clinical Oncology (ASCO) Clinical Guidelines for chemotherapy-induced peripheral neuropathy (CIPN) management (48 Phase III trials reviewed) only recommend duloxetine. However, before concluding that a CIPN intervention is ineffective, scientists and clinicians should consider the risk of Type II error in Phase III studies. The purpose of this systematic review was to characterize internal threats to validity in Phase III CIPN management trials. Methods: The PubMed, CINAHL, EMBASE®, and Scopus databases were searched for Phase III clinical trials testing interventions for CIPN management between 1990 and 2018. The key search terms were neoplasms, cancer, neuropathy, and CIPN. Two independent researchers evaluated 24 studies, using a modified Joanna Briggs Institute Checklist for Randomized Control Trials developed by the authors specific for CIPN intervention trials. Results: Two studies exhibited minimal or no design flaws. 22/24 Phase III clinical trials for CIPN have two or greater design flaws due to sample heterogeneity, malapropos mechanism of action, malapropos intervention dose, malapropos timing of the outcome measurement, confounding variables, lack of a valid and reliable measurement, and suboptimal statistical validity. Conclusions: Numerous CIPN interventions have been declared ineffective based on the results of Phase III trials. However, internal validity threats to numerous studies may have resulted in Type II error and subsequent dismissal of a potentially effective intervention. Patients may benefit from rigorous retesting of several agents (e.g., alpha-lipoic acid, duloxetine, gabapentin, glutathione, goshajinkigan, lamotrigine, nortriptyline, venlafaxine, and Vitamin E) to expand and validate the evidence regarding ASCO's recommendations for CIPN management.